A case report of Neurologic manifestations after multiple Bee Stings - T. SPURTHI,; K.REKHA RANI,; Y.NAVYA,; S. KUSUMA KUMARI,; P. RANI, (International Journal of Pharma and Bio Sciences, 2018)
Honeybees are very common flying insects, encountered in daily life and accidents associated with them are also equally frequent. The sting venom mostly causes local anaphylactic reactions, and rarely shows neurological symptoms. We report a case of such rare reaction in a 48 yr old diabetic male patient with complaints of aphasia, lower limb weakness and cough, after 12 hours of honey bee attack. In the CT- scan acute multi focal infarcts were observed, confirming the condition to be ischemic stroke. The treatment included mannitol, aspirin, atorvastatin for ischemic stroke along with symptomatic therapy for respiratory problem. The patient was discharged from the hospital after his limb monoparesis gradually improved and advised to visit after 2 months for further follow up. The systemic immune mediated reactions, along with bee venom toxins like mellitin & phospholipase mediated intravascular coagulation effect might be the possible mechanism contributing to cerebral ischemia.